Visuality, Drama, and Judicial Ritual in Mayan Law: A Case Study in Santa Cruz del Quiché, Guatemala - Flores, Carlos Y. (2024)
Introduction: Given limited access to the State justice system, some K’iche’ communities in Western Guatemala resort to community trials within Mayan law to publicly prosecute people accused of committing crimes in practices known locally as suk’ b’anik (correction/ straightening out), which often feature highly ritualized spectacular choreographies directed in the first instance at the local population. Objective: The article seeks to analyze Mayan cultural understandings around community trials in Santa Cruz del Quiché that, under the leadership of local indigenous mayors, seek to reintegrate criminals after their judicial prose- cution and public repentance. Results: By following the community judicial prosecution of two local criminals, the paper aims to analyze the logics, emotions, and collective gestures that are framed through mechanisms of representation and circulation –among them video– which operate within visual regimes of truth/power in conflictive social contexts.